Pengaruh Customer Satisfaction Dan Customer Experience Terhadap Minat Beli Ulang Garnier Men Di Kota Langsa - Fadly, M.; Lindung Bulan, Tengku Putri; Amilia, Suri (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study aims to determine the effect of customer satisfaction and customer experience on the intention to repurchase Garnier Men in Langsa City. The sample in this study amounted to 96 respondents. The data analysis method used multiple linear regression analysis, t test, F test, and analysis of the coefficient of determination (adjusted R2). Customer satisfaction has a significant effect on the intention to repurchase Garnier Men in Langsa City, where from the t-test the t-sig value is 0.001. Customer Experience has a significant effect on the intention to repurchase Garnier Men in Langsa City, where from the t-test the t-sig value is 0.000. Customer Satisfaction and Customer Experience simultaneously have a significant effect on the intention to repurchase Garnier Men in Langsa City, where from the F test the F sig value is obtained. 0.000 < 0.05. From the coefficient of determination analysis, it is known that the variables of customer satisfaction and customer experience affect the buying interest of Garnier Men in Langsa City by 63.8% while the remaining 36.2% is influenced by other variables outside this research model.